A Handbook of the Mythological and Biblical Allusions in Lamb's Essays of Elia - Overton, Laura Hudgins (My University, 1935)
The study is divided into two parts: the first deals with The Essays of Elia, and the second, with the Last Essays of Elia. The explanations are given in the order of the allusions in the essays. Those essays in which no references to mythology or to the Bible have been found are specially noted. No attempt has been made to give more than one version of a myth or to discover what source Lamb, himself, used.
Keywords: Literary Criticism; Essays of Elia; Lamb, Charles